1976
DOI: 10.1111/j.1476-5381.1976.tb07439.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of Α‐adrenoceptor Antagonists in Rat Isolated Vas Deferens

Abstract: I In rat isolated vas deferens, the isotonic contractile responses to low doses of noradrenaline or adrenaline were antagonized, and those to high doses were potentiated, by yohimbine, piperoxan, phentolamine and tolazoline. Effects due to intermediate doses were not affected, or were potentiated within about 30 min, following an initial inhibition. 2 The a-adrenoceptor blockers thus caused a shift to the right and an increase of the maximum height of log dose-response curves of a-adrenoceptor stimulants. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 24 publications
5
21
0
Order By: Relevance
“…[16][17][18] One end of the vas deferens was fixed to the organ chamber, and the other end was attached by means of a silk surgical suture to a force-displacement transducer (model FT 302; CB FT-302, iWORX, NH, USA) connected through a bridge amplifier to a PowerLab recorder (ADInstruments, Castle Hill, NSW, Australia) coupled to a computer. Contractions were recorded and the data stored in Chart 4.2.1 software (ADInstruments, Warwick, USA).…”
Section: Functional Study Of Sympathetic System and Pharmacological Rmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18] One end of the vas deferens was fixed to the organ chamber, and the other end was attached by means of a silk surgical suture to a force-displacement transducer (model FT 302; CB FT-302, iWORX, NH, USA) connected through a bridge amplifier to a PowerLab recorder (ADInstruments, Castle Hill, NSW, Australia) coupled to a computer. Contractions were recorded and the data stored in Chart 4.2.1 software (ADInstruments, Warwick, USA).…”
Section: Functional Study Of Sympathetic System and Pharmacological Rmentioning
confidence: 99%
“…Cumulative concentration-response curves were made for the adrenergic agonist noradrenaline (NA) (10 −8 −3.10 −4 M), 16 to quantify for possible alterations of receptors, indicated by the respective pharmacological parameters, 19 such as E am (maximum contraction induced by an agonist A) 16 and pD 2 , as the apparent affinity of the agonists, measured as the negative log of ED 50 . 19 Contractions induced by single concentration of the indirect agonist tyramine (10 −4 M) were also measured, to check for changes on the release of endogenous NA.…”
Section: Pharmacological Reactivitymentioning
confidence: 99%
“…However, (+)-glaucine did not reduce the accumulation of tritium in tissues exposed to [3H]-noradrenaline and, hence, presumably did not significantly inhibit this uptake mechanism. Other mechanisms are therefore implicated, such as a sensitization to the effects of noradrenaline (see Jurkiewicz & Jurkiewicz, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter case, Iso, Ad, and NA elicited a dose-dependent decrease of the amplitude of twitches, without affecting the baseline (Diaz-Toledo & Jurkiewicz, 1980;1990). However, if the concentrations of these agonists were further increased, an undesirable rise in the baseline occurred, due to a well-known concentrationdependent interaction with postsynaptic a-adrenoceptors (Jurkiewicz & Jurkiewicz, 1976); the minimum concentrations of these agonists to start such an increase in the baseline were about 3 x 10-7M for Ad and NA, and 3 x 10-5M for Iso (Diaz-Toledo, 1983). To overcome this problem, aadrenoceptors had to be inactivated in an essentially irreversible manner by a fi-haloalkylamine.…”
Section: Concentration-response Curvesmentioning
confidence: 99%
“…As an additional control, it was observed that the presynaptic aadrenoceptor agonist, clonidine, was unable to induce inhibitory effects upon electrically-induced twitches, when added up to a concentration of 3 x 10-5M, while in preparations which were not treated with dibenamine, a complete inhibition of twitches was observed with a dose of clonidine about 300 times lower (Diaz-Toledo, 1983). To block neuronal uptake, cocaine (10puM) was added to the bath (Jurkiewicz & Jurkiewicz, 1976), 30min before the beginning of concentrationresponse curves, and maintained thereafter. In relation to extraneuronal uptake, other drugs were not used, since dibenamine is known to be an irreversible blocker of this type of removal mechanism (Furchgott, 1972;Furchgott et al, 1974 (Arunlakshana & Schild, 1959;Furchgott et al, 1974):…”
Section: Concentration-response Curvesmentioning
confidence: 99%